Thomson's dictionary of banking - Thomson, William; Perry, F. E.; Ryder, F. R. (London : Pitman, 1965)
In the thirteen years which have passed since the last edition of this work, great changes have passed over the face of banking and, indeed, over the life of the nation as a whole. The Editors have tried to give expression to these changes in the revision of the dictionary. There has been much new legislation to note, and, in addition to those changes of importance on the general banking side, an attempt has been made to expand the information of interest to those engaged in executor and trustee work.
Includes bibliographical references: p. viii.
ne 26/08/2021
Ref.
Keywords: Banks and banking; Banking law; Land titles